Reported severity of psychotic, depressive and anxiety symptoms in relation to bilingual language profile: An exploratory study and the validation of Basque versions of the PQ-B, DASS-42, PHQ-9 and GAD-7 - Leire Erkoreka; Naiara Ozamiz-Etxebarria; Onintze Ruiz; Maider Prieto; Saioa Aspiazu; Argiñe Mingo; Urko Aguirre; Miren Orive; Simona Mancini (PLoS ONE, 2025)
Background Language plays a crucial role in health care and especially in mental health, since the use of the native language helps to make a good diagnosis as several studies have shown. Aim We studied the influence of language on the accurate detection of psychotic and affective symptoms, exploring differences in the severity of reported symptomatology in a bilingual Basque-Spanish population. Methods The study uses the Prodromal Questionnaire-Brief for the detection of psychosis and the Patient Health Questionnaire-9, Generalized Anxiety Disorder Scale-7, and Depression, Anxiety and Stress Scale-42 for the assessment of stress, anxiety and depression. Basque versions of the scales were developed and their psychometric properties were evaluated in a sample of 623 individuals, including 521 from the general population and 102 psychiatric patients. Possible relations between questionnaire scores and four linguistic factors, namely first language (L1), proficiency, age of acquisition and language exposure, were examined. Results The four translated questionnaires showed adequate sensitivity, goodness-of-fit, and reliability indices, thus validating their suitability for general and clinical settings. The results showed that reporting of depressive symptoms seemed to be modulated by linguistic variables, mainly L1, whereas the severity of psychotic symptoms was less reliably associated with the gathered linguistic factors. Conclusions Overall, our results suggest that language of assessment by means of written instruments may have a limited impact on healthcare outcomes in balanced bilingual populations. The study enriches the understanding by considering various linguistic factors beyond L1, and by exploring the effect of these factors on affective symptoms, apart from psychotic ones.